Remainder - McCarthy,Tom (Richmond, Surrey : Alma Books, 2016)
Film Tie-in edition to be published to coincide with the release of the film Remainder. Praised by Zadie Smith as "one of the great English novels of the past ten year", this edition contains a foreword by American scholar McKenzie Wark.
Film tie-in.
This edition originally published: 2015.
ENH
Karim International
Keywords: Accident victims -- Fiction; Amnesia -- Fiction; Accident victims; English literature